2016
DOI: 10.1160/th16-01-0015
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS5 promotes murine adipogenesis and visceral adipose tissue expansion

Abstract: Enhanced expression of the aggrecanase ADAMTS5 (A Disintegrin And Metalloproteinase with Thrombospondin type 1 motifs; member 5) has been observed in adipose tissue (AT) of obese rodents. Here, we have investigated the role of ADAMTS5 in adipogenesis, AT expansion and associated angiogenesis. In vitro differentiation of precursor cells into mature adipocytes was studied using murine embryonic fibroblasts (MEF) derived from wild-type (Adamts5(+/+)) and ADAMTS5 deficient (Adamts5(-/-)) mice, or 3T3-F442A preadip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 50 publications
5
11
1
Order By: Relevance
“…The role of ADAMTS5 in AT development and diet‐induced fatty liver disease was previously investigated. We confirm in this study that ADAMTS5‐deficient mice developed less subcutaneous and visceral AT and had a smaller liver when fed a HFD as compared to WT mice, as reported previously (Bauters et al, , , ). Furthermore, analysis of the liver revealed less triglyceride accumulation, hepatocyte ballooning, inflammation and fibrosis in livers of Adamts5 − / − ‐J versus Adamts5 +/+ ‐J mice on a HFD.…”
Section: Discussionsupporting
confidence: 92%
“…The role of ADAMTS5 in AT development and diet‐induced fatty liver disease was previously investigated. We confirm in this study that ADAMTS5‐deficient mice developed less subcutaneous and visceral AT and had a smaller liver when fed a HFD as compared to WT mice, as reported previously (Bauters et al, , , ). Furthermore, analysis of the liver revealed less triglyceride accumulation, hepatocyte ballooning, inflammation and fibrosis in livers of Adamts5 − / − ‐J versus Adamts5 +/+ ‐J mice on a HFD.…”
Section: Discussionsupporting
confidence: 92%
“…The question remained whether the observed effects of ADAMTS5 deficiency on WAT browning were a direct effect. We have previously shown that differentiation of 3T3-F442A preadipocytes into mature adipocytes is impaired with stable Adamts5 gene silencing, and that de novo adipogenesis (fat formation) in Nude mice following injection of 3T3-F442A cells with Adamts5 knockdown was significantly reduced, as compared to control cells [14]. This is compatible with the observed reduction in SC and GON AT mass in Adamts5 −/− mice on HFD.…”
Section: Discussionsupporting
confidence: 83%
“…In general, stimulating thermogenesis in brown and/or beige adipocytes, thereby utilizing large amounts of stored energy (fatty acids and glucose), seems an attractive strategy to increase energy expenditure and thus to treat obesity and diabetes [5], [33], [49], [50]. We confirmed that after a Western-type diet, the weights of gonadal and subcutaneous adipose tissue depots were significantly lower for Adamts5 −/− mice compared to wild-type mice [14]. Hence, the identification of ADAMTS5 as a negative regulator of BAT mass and browning of WAT is potentially very promising for the development of new therapeutic strategies.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations